A Case Study of Thiourea‐Assisted Iminium Formation by Hydroxyl Anion Binding: Kinetic, Spectroscopic and Computational Evidences. Issue 23 (29th September 2017) - Juste‐Navarro, Veronica; Prieto, Liher; Delso, Ignacio; Manzano, Rubén; Tejero, Tomas; Reyes, Efraim; Vicario, Jose L.; Merino, Pedro
Abstract: The experimental and computational study of the mechanism of the iminium‐organocatalyzed formation of N ‐hydroxypyrrolidines from nitrones, revealed up to three activation levels of the Schreiner's thiourea used as co‐catalyst, i.e: (i) formation of the iminium ion through hydroxyl anion recognition forming a stable ion pair; (ii) enolization of the nitrone through a H‐bond network and (iii) activation of the nitrone moiety towards the final ring closure. The computational model supports the mechanism and the catalytic cycle. This mechanistic rationale is supported by the lack of reactivity of preformed iminium ion with the nitrone in the absence of thiourea‐hydroxyl complex and the observed reactivity when a complex thiourea‐tetrabutylammonium hydroxide is added. Abstract :